Carpal Tunnel Syndrome Pada Petani : Tinjauan Pustaka - Azzahra, Herina; Utama, Winda Trijayanthi (CV. Jasa Sukses Abadi, 2026)
Carpal Tunnel Syndrome (CTS) is a compression neuropathy resulting from increased pressure on the median nerve within the carpal tunnel, characterized by pain, paresthesia, and numbness affecting the thumb to the third finger. CTS represents one of the most common musculoskeletal disorders, particularly among workers engaged in repetitive hand movements, forceful manual tasks, or prolonged non-ergonomic wrist postures. Globally, its prevalence varies across populations and may reach 7–20% among industrial workers. In Indonesia, CTS remains an underreported condition and is often regarded as an iceberg phenomenon due to limited clinical detection and reporting. CTS may be idiopathic or secondary to conditions such as pregnancy, obesity, hypothyroidism, and diabetes mellitus. Diagnosis is primarily clinical, supported by provocative tests such as Phalen’s test, Tinel’s sign, and the wrist extension test, as well as neurophysiological assessments including electromyography and nerve conduction studies. Radiological imaging may assist in excluding other structural causes. Management consists of conservative measures such as activity modification, wrist exercises, splinting, and the use of analgesics or anti-inflammatory agents. In moderate to severe cases, surgical decompression through division of the transverse carpal ligament is required to reduce pressure on the median nerve. Preventive strategies focus on improving workplace ergonomics, controlling comorbid conditions, and providing education regarding safe hand-use practices.